2015
DOI: 10.1038/ncb3101
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin functions as a scaffold for selective macroautophagy

Abstract: Selective macroautophagy is an important protective mechanism against diverse cellular stresses. In contrast to the well-characterized starvation-induced autophagy, the regulation of selective autophagy is largely unknown. Here, we demonstrate that Huntingtin, the Huntington’s disease gene product, functions as a scaffold protein for selective macroautophagy but it is dispensable for nonselective macroautophagy. In Drosophila, Huntingtin genetically interacts with autophagy pathway components. In mammalian cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
347
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 357 publications
(365 citation statements)
references
References 82 publications
11
347
1
6
Order By: Relevance
“…However, the underlying mechanism is yet to be uncovered. Recently, Huntingtin, the Huntington's disease gene product, was identifi ed as a scaffold protein for selective autophagy including aggrephagy, mitophagy, and lipophagy in mammalian cells, paving the way for further investigation in this emerging young field [8] . In addition, cargo receptor proteins such as p62 and NBR1 bring cargos to autophagosomes by interacting with the autophagosomal protein LC3 [9] .…”
mentioning
confidence: 99%
“…However, the underlying mechanism is yet to be uncovered. Recently, Huntingtin, the Huntington's disease gene product, was identifi ed as a scaffold protein for selective autophagy including aggrephagy, mitophagy, and lipophagy in mammalian cells, paving the way for further investigation in this emerging young field [8] . In addition, cargo receptor proteins such as p62 and NBR1 bring cargos to autophagosomes by interacting with the autophagosomal protein LC3 [9] .…”
mentioning
confidence: 99%
“…65 In addition, a new study reported that WT-HTT serves as an important scaffold protein in multiple types of selective macroautophagy (not including starvation-induced autophagy) in Drosophila and mammalian cells (including mouse embryonic fibroblasts and striatal cells). 66 WT-HTT is able to bind simultaneously two important ATG proteins, p62 and unc-51-like autophagy activating kinase (ULK1). 66 In sum, studies to date indicate abnormal autophagy function in HD and suggest that HTT has a functional role in autophagy.…”
mentioning
confidence: 99%
“…66 WT-HTT is able to bind simultaneously two important ATG proteins, p62 and unc-51-like autophagy activating kinase (ULK1). 66 In sum, studies to date indicate abnormal autophagy function in HD and suggest that HTT has a functional role in autophagy. Upregulation of autophagy has been shown to enhance polyQ-HTT clearance 53 and drugs targeting autophagy--such as rapamycin/CCI-779, lithium, trehalose and rilmenidine--continue to be of interest as potential therapeutic agents for HD.…”
mentioning
confidence: 99%
“…HTT is a scaffolding protein that is involved in multiple cellular functions [65,81,82]. The generation and characterization of Htt knock-out mice revealed that Htt has an essential function during early embryonic development [83][84][85].…”
Section: Wild Type Huntington Functionsmentioning
confidence: 99%
“…HTT has been shown to promote selective macroautophagy through its interaction with several autophagy pathway members including p62/SQSTM1 (p62), Ubiquitin (Ub) and microtubule associated protein 1A/1B-light chain 3 (LC3) [81]. "Bulk" non-selective macroautophagy (a.k.a.…”
Section: Wild Type Huntington Functionsmentioning
confidence: 99%